Analysis of the Effectiveness of Multifrequency OFDM Systems with a Constant Envelope in a Hydroacoustic Simulator and During In Situ Tests - A. Yu. Rodionov; L. G. Statsenko; A. A. Chusov; D. A. Kuzin; M. M. Smirnova (Acoustics)
The key elements in the operation of modern underwater robotic systems are hydroacoustic communication and navigation systems. Hydroacoustic data transmission channels are designed in such a way that the transmitted information signals must be resistant to various types of interference and distortion, even without preliminary estimates of the channel parameters, due to their significant non-stationarity because of the roughness of the sea surface, currents, and the movement of underwater vehicles. Furthermore, due to the high mobility of underwater vehicles, the transmission time of navigation signals and necessary information packets must be significantly reduced, which can negatively affect the noise immunity of the packages. For these purposes, digital wideband signals and orthogonal frequency division multiplexing (OFDM) are widely used; however, a number of significant drawbacks of these types of modulations often do not allow for the forming of a reliable channel for transmitting information, and for the navigation of mobile underwater systems. Unfortunately, this problem is not comprehensively presented in the literature. The authors propose to use the algorithm of digital data transmission based on the OFDM constant envelope multifrequency modulation (CE-OFDM) with differential symbol coding, which is suitable for non-stationary hydroacoustic environments. The presented algorithm, due to the minimization of the signal peak factor, can improve the signal-to-noise ratio at the receiving end by 5–10 dB, with a number of other advantages, over the classical OFDM method. The authors also numerically found groups of short binary sequences from 14–55 elements long, with the best autocorrelation properties for the formation of synchronization and navigation preambles with high noise immunity to Doppler and multipath effects that are characteristic of the hydroacoustic communication channel. The proposed algorithms were tested on the certain channel models on the Watermark acoustic simulator, as well as in shallow water at distances up to 2 km.